EFESIENSI DAN EFEKTIVITAS PENGGUNAAN ALAT BERAT BALAI PELAKSANA JALAN NASIONAL XXI KENDARI PADA PEKERJAAN JALAN NASIONAL DI KONAWE UTARA - Paisal, Paisal; Putra, Adris Ade; Magribi, La Ode Muh (Pascasarjana Universitas Halu Oleo, 2022)
Road network handling activities aim to improve and maintain road conditions so that accessibility and mobility are maintained to meet the needs of the community for movement At the XXI National Road Executing Center in Kendari, the use of heavy equipment is for routine road maintenance activities. So far, the activity of maintaining and building roads in the province of Southeast Sulawesi. XXI Kendari National Road Executing Agency's heavy equipment consists of several types, including: Motor Graders, Wheel Loaders, Three Wheel Rollers, Dump Trucks, Excavators, Boldoser, and Tandem Rollers. Based on the heavy equipment characteristics of the Excavator National Road Executing Agency, the Bulldozer is badly damaged, the Road Roller (3 Damaged and 4 is good), the Motor Greder is good and the Whell Loader (1 Damaged and 1 Good)The level of effectiveness of heavy equipment managed by the XXI Kendari National Road Executing Agency is still low, this is indicated by the average level of tool utility valued at 22.75%, as well as the average efficiency level of only 23.93%, this is caused by, Some tools are old and have passed the economic age so that they have an impact on the high operational costs of the equipment, the level of utility of the tool is low, because the use of equipment is still limited in North Konawe district, Supervision of operating hours and the imposition of late payment penalties accordingkeywords: Heavy equipment, Efficiency, Effectiveness